A Multi-Pulse Phase-Modulation/Duty Cycle Control for a Triple Active Bridge Converter - Al-Jafeary I.M.K.; Tan N.M.L.; Mansor M.B.; Buticchi G. (Institute of Electrical and Electronics Engineers Inc., 2023)
DC-DC converters; More electric aircraft; Phase modulation; Switching; Bidirectional isolated dc-dc converter; Bridge converter; Duty cycle control; Duty-cycle; More electric aircraft; Multiple active bridge; Multipulses; Pulse phase; Single pulse; Switching techniques; Energy transfer